The Presence of White Matter Lesions Is Associated With the Fibrosis Severity of Nonalcoholic Fatty Liver Disease. Issue 16 (April 2016) - Petta, Salvatore; Tuttolomondo, Antonino; Gagliardo, Cesare; Zafonte, Rita; Brancatelli, Giuseppe; Cabibi, Daniela; Cammà, Calogero; Di Marco, Vito; Galvano, Luigi; La Tona, Giuseppe; Licata, Anna; Magliozzo, Franco; et al.
Abstract : Abstract: We tested whether nonalcoholic fatty liver disease (NAFLD) and/or its histological severity are associated with vascular white matter lesions (WML) in patients with biopsy-proven NAFLD and in non-NAFLD controls. Data were recorded in 79 consecutive biopsy-proven NAFLD, and in 82 controls with normal ALT and no history of chronic liver diseases, without ultrasonographic evidence of steatosis and liver stiffness value <6 KPa. All subjects underwent magnetic resonance assessment and WML were classified according to the Fazekas score as absent (0/III), or present (mild I/III; moderate II/III, and severe I/III). For the purpose of analyses, all controls were considered without NASH and without F2–F4 liver fibrosis. WML were found in 26.7% of the entire cohort (43/161), of moderate–severe grade in only 6 cases. The prevalence was similar in NAFLD versus no-NAFLD (29.1% vs 24.3%; P = 0.49), but higher in NASH vs no-NASH (37.7% vs 21.2%, P = 0.02) and F2–F4 vs F0-F1 fibrosis (47.3% vs 20.3%, P = 0.001). In both the entire cohort and in NAFLD, only female gender (OR 4.37, 95% CI: 1.79–10.6, P = 0.001; and OR 5.21, 95% CI: 1.39–19.6, P = 0.01), age > 45 years (OR 3.09, 95% CI: 1.06–9.06, P = 0.03; and OR 11.1, 95% CI: 1.14–108.7, P = 0.03), and F2–F4 fibrosis (OR 3.36, 95% CI: 1.29–8.73, P = 0.01; and OR 5.34, 95% CI: 1.40–20.3, P = 0.01) were independently associated with WML (mostly of mild grade) by multivariate analysis. Among NAFLD, the prevalence of WML progressively increased from patients without (1/18; 5.5%), or with 1 (1/17, 5.8%), to those with 2 (9/30; 30%) and further to those with 3 (12/14; 85.7%) risk factors. The presence of WML is not associated with NAFLD, but with metabolic diseases in general, and fibrosis severity of NAFLD. Clinical implications of this issue need to be assessed by longitudinal studies.